Analisis Hidrologi untuk Pendugaan Debit Banjir dengan Metode Nakayasu di Daerah Aliran Sungai Way Besai - Repinka Cornelia; Suprapto Suprapto; Kelik Istanto (Jurnal Ilmiah Teknik Pertanian - TekTan, 2014)
Way Besai is one tributary Way Kanan located in West Lampung and Way KananÂ  Regency, Lampung Province. Way Besai riverbanks downstream of the low areas during the rainy season in some locations overflowing river submerged. This condition is exacerbated by the destruction of the river catchment Way Besai resulting in flooding during the rainy season. The purpose of this study to estimate precipitation plan, and estimate the flood discharge plan using Nakayasu. Activities undertaken include the determination of the maximum daily rainfall, creation of Thiessen polygons, calculation of the maximum average rainfall, the calculation of the frequency distribution, determination of the suitability of the Chi Square test the method Gumbel and Log Pearson III method, the calculation of the design rainfall distribution, as well as the calculation of flood discharge by using Nakayasu method. The results of the calculation of rainfall plan (after the Chi Square test) were obtained for 10-year return period of 83.46 mm/day. Return period of 25 years at 105.41 mm/day. 50-year return period of 123.70 mm/day. Flood discharge plan obtained by unit hydrograph method Nakayasu of 244.15 m3/sec for a period of 10years, 308.35 m3/sec for 25-year return period and 361.83 m3/sec for a period of over 50 years. The time required for the peak flood from upstream to downstream for 19 hours.Â Keywords: analysis of hydrology, rainfall plan, and flood discharge plan